"Skilled white bodies": Portuguese workers in Angola as a case of North–South migration. Issue 1 (21st November 2019) - Augusto, Asaf; King, Russell
Abstract : The economic crisis which has affected the southern EU countries since 2008 set in motion new migration trends. In the case of Portugal, post‐crisis migrations have been in two main directions: northwards to more prosperous European countries, and southwards to former colonies in Africa, notably the oil‐producing state of Angola. Focusing on this latter migration, the paper is structured around two main questions. First, which migration‐theoretic frameworks can be deployed to explain this new North–South migration flow? Relevant concepts include the notion of Portugal as "semi‐periphery" within European and global migration systems; the role of post‐colonial theory, especially ideas about "coloniality" and "Lusotropicalism"; and the function of myth and racialised discourse in constructing this as a high‐skilled migration. The second question is more empirical and relates to the descriptive characteristics of the Portuguese migration to Angola and to the experiences of the migrants and their Angolan co‐workers and employers. Key here is a deconstruction of the notion of "skill" in Portuguese migrants' experiences of employment in Angola. The empirical analysis is based on interviews with 45 migrants, their co‐workers and employers, and other key informants.